2015
DOI: 10.1007/s13277-015-4543-3
|View full text |Cite
|
Sign up to set email alerts
|

A synonymous EGFR polymorphism predicting responsiveness to anti-EGFR therapy in metastatic colorectal cancer patients

Abstract: Genetic factors are known to affect the efficiency of therapy with monoclonal antibodies (mAbs) targeting the epidermal growth factor receptor (EGFR) in patients with metastatic colorectal cancer (mCRC). At present, the only accepted molecular marker predictive of the response to anti-EGFR mAbs is the somatic mutation of KRAS and NRAS as a marker of resistance to anti-EGFR. However, only a fraction of KRAS wild-type patients benefit from that treatment. In this study, we show that the EGFR gene polymorphism rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
0
20
1
Order By: Relevance
“…Although we did not observe association of p.Q787Q with clinicopathological or treatment parameters, we assessed possible modes of function as previously described by Bonin et al (Bonin et al, 2015). For the proposed mechanism of changed codon usage, we found that the original CAG codon is used more often than the CAA resulting from the polymorphism (73% vs. 27%; Codon usage database).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Although we did not observe association of p.Q787Q with clinicopathological or treatment parameters, we assessed possible modes of function as previously described by Bonin et al (Bonin et al, 2015). For the proposed mechanism of changed codon usage, we found that the original CAG codon is used more often than the CAA resulting from the polymorphism (73% vs. 27%; Codon usage database).…”
Section: Resultsmentioning
confidence: 92%
“…Contrasting the data by Koh et al (2016), Bonin et al (Bonin et al, 2015) observed improved overall survival in CRC patients homozygous for p.Q787Q. This study retrospectively analyzed a colon cancer cohort comprising controls treated with chemotherapy (n 5 65) and a cohort treated with the anti-EGFR antibodies cetuximab or panitumumab (n 5 98).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…EGFR genetic polymorphisms have been investigated for carcinogenesis in various tumors including colon cancer [11], gastric cancer [12], head and neck squamous cell carcinoma [13], biliary tract cancer [14], and cervical cancer [15]. Furthermore, EGFR genetic polymorphisms have shown a predictive value for the risk of breast cancer [16].…”
Section: Introductionmentioning
confidence: 99%